Comparison of the effect of applying the Ovsynch protocol on some reproductive parameters of pups and dairy cows in different production seasons - تامر, نورشان; زهير جبور ,; سراج ريا , (Latakia University Journal -Biological Sciences Series, 2023)
This study aimed to compare the effect of application of the Ovsynch protocol on reproductive parameters (pregnancy rate, insemination index, service period, period between two calvings, and onset of estrus) in heifers and Holstein-Friesian dairy cows bred under local conditions and the dynamics of response in relation to the productive season. For this purpose, the hormonal treatment was done with the Iranian vetocept compound, as 2ml of the synthetic GnRH compound (buserlin acetat) was injected intramuscularly at a concentration of 0.0042 per 1ml of the dose. The study was conducted on cows within private breeding farms in the countryside of Jableh, in cooperation with the Video Farm of the Ministry of Agriculture, starting from the tenth month of 2020 until the ninth month of 2022, on 30 and 30 cows from different production seasons. When applying the Ovsynch protocol, the study recorded a 30% decrease in response to pregnancy in the heifers, compared to 60% in dairy cows at a probability value of P<0.001, while it was found that there were no significant differences in the effect of the Ovsynch protocol on the different production seasons M1, M2, and M3 (60, 60). %, 60%, respectively, at a probability value of P<0.05. The results also showed that there were no significant differences in the insemination index for each of the first-born and dairy cows in their three productive seasons M1, M2, and M3 (3,7, 3,6, 3,5, 3,5), respectively, at a probability value of P< 0, 05. It also showed that there were no significant differences in the period of service between the productive seasons M1, M2, and M3 (144.7, 142.6, 134.9) and in the period between two births (415.1, 412.7, 404.8) at the probability value. P< 0, 05. However, the results showed that there were significant differences in the interval between two inoculations before (51, 41.2, 38.70, 39.8) and after applying the Ovsynch protocol (27, 8.502, 23.25, 24.75) in the precocials and M1 production seasons. M2, M3 on the season 1 and 2 groups at a probability value of P ≤ 0.05, and there were significant differences on the group of seasons 3 and chicks at a probability value of P ≤ 0.001. That is, the appearance of sway became clearer and the percentage of silent sway decreased when applying the Ovsynch protocol.